The biological link between urban spaces. - Schippers, Heinrich (My University, 2010)
According to the UN report released on 26 February 2008, half of the world’s population has been living in cities at the beginning of this year. This rapid urban growth puts high pressure on the built and even more on the natural environment. After a long time replacing earth’s natural eco systems with artificial equivalents with little thought to long-term consequences, urban citizens today are mostly depending on government infrastructures to sustain their daily consumption needs. Local eco-systems are already unable to sustain future needs to consume non-renewable energy resources. In a (partially) developing country like South Africa, it is of utmost importance to adopt a more sustainable life-style through environmentally integrating building systems and urban infrastructural alternatives, which respond and enhance local ecosystems. This thesis works within Johannesburg’s inner city and intends to use architectural forms and practices to make the most of the ambient energy stored in nature with minimal use of conventional or alternative non-renewable energy resources. Thermal comfort will be achieved by observing and understanding what affects the local rainfall, wind, sun path, temperature, humidity, location, orientation, and the choice of urban materials/surfaces have on a selected part of urban surroundings and built forms. Diagonal Street will serve as testing ground. Through utilising architectural methods and technologies as a means to achieve low energy impact on the surrounding ecology of buildings, a manual can be designed on how to promote better thermal comfort levels and enhance the quality of space in existing urban fabrics by creating either new built forms or refurbishing/adapting existing buildings. The integration of environmental building practices in the future planning of Johannesburg City becomes a powerful argument on why there needs to be a better variety of ecological diversity in urban cities today and in Johannesburg in particular. This thesis will refer to those practices as biophilic architecture. The biologist E.O. Wilson introduced the word biophilia in 1984, dealing with the affiliation of nature and other living forms. The objective of this thesis is to stem a better symbiotic relationship between nature and the built environment.